2017
DOI: 10.1088/1361-6560/aa9676
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the generalisation of an atlas-based synthetic-CT algorithm to another centre and MR scanner for prostate MR-only radiotherapy

Abstract: There is increasing interest in MR-only radiotherapy planning since it provides superb soft-tissue contrast without the registration uncertainties inherent in a CT-MR registration. However, MR images cannot readily provide the electron density information necessary for radiotherapy dose calculation. An algorithm which generates synthetic CTs for dose calculations from MR images of the prostate using an atlas of 3 T MR images has been previously reported by two of the authors. This paper aimed to evaluate this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Dosimetric accuracy of prostate synthetic CT solutions was investigated by the majority of studies and considered to be clinically acceptable in all cases. 6,16,[18][19][20][21] The similar results of these studies, despite significant differences in study design including various synthetic CT generation methods, shows that the dosimetric accuracy of synthetic CT techniques is broadly reproducible across a wide range of clinical systems and techniques, including multiple commercial options available for prostates. 10,11 The presented studies also provide a suitable blueprint for centers wishing to begin clinical implementation of MR-only planning themselves regarding dosimetric accuracy assessment.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Dosimetric accuracy of prostate synthetic CT solutions was investigated by the majority of studies and considered to be clinically acceptable in all cases. 6,16,[18][19][20][21] The similar results of these studies, despite significant differences in study design including various synthetic CT generation methods, shows that the dosimetric accuracy of synthetic CT techniques is broadly reproducible across a wide range of clinical systems and techniques, including multiple commercial options available for prostates. 10,11 The presented studies also provide a suitable blueprint for centers wishing to begin clinical implementation of MR-only planning themselves regarding dosimetric accuracy assessment.…”
Section: Discussionmentioning
confidence: 59%
“…In the case of Persson et al, 6 case, this was from a multicenter research-only study for commissioning purposes, whereas other experiences 14,17 resulted from treating their first MR-only patients. Wyatt et al 20 reported MR scan success rates from retrospectively assessed MR data, whereas Christiansen et al 16 reported synthetic CT generation success rate but did not discuss issues regarding MR acquisition. In describing their clinical workflow for MRonly planning, Tyagi et al 17 also reported a time savings when using an MR-only versus CT-MRIebased workflow.…”
Section: Mr Acquisition and Synthetic Ct Generation Verificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Deep learning-based sCT generation in RT and PET August 18, 2021 page been envisioned to improve the quality of CBCT 29 . Cone-beam computed tomography plays a vital role in image-guided adaptive radiation therapy (IGART) for photon and proton therapy.…”
Section: Accepted Articlementioning
confidence: 99%
“…This was followed by voxel based weighting of atlas HU values according to the acquired voxel MRI similarities to the registered atlas voxels(Dowling et al , 2015). The applicability of this method to 1.5T has recently been demonstrated(Wyatt et al , 2017). A similar approach termed ‘statistical decomposition algorithm’ uses atlas scans that are deformably registered to the acquired MRI with a first registration used to drive segmentation of tissue classes on the acquired MRI and then a second structure-guided registration using the segmentations.…”
Section: Introductionmentioning
confidence: 99%